2007
DOI: 10.1137/060668158
|View full text |Cite
|
Sign up to set email alerts
|

Period-Doubling of Spiral Waves and Defects

Abstract: Abstract. Motivated by experimental observations in the light-sensitive Belousov-Zhabotinsky reaction and subsequent numerical works, we discuss period-doubling bifurcations of spiral waves and other coherent structures. We report on explanations of the observed phenomena which involve a detailed analysis of spectra, and of the associated eigenfunctions, of defects on bounded and unbounded domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 42 publications
(99 reference statements)
0
31
0
Order By: Relevance
“…The dynamical behavior of the spiral waves has been previously investigated for the diffusive Rössler model [18]. Here we reconsidered the effect of the time-delay and the cross-diffusion.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The dynamical behavior of the spiral waves has been previously investigated for the diffusive Rössler model [18]. Here we reconsidered the effect of the time-delay and the cross-diffusion.…”
Section: Discussionmentioning
confidence: 97%
“…The break-up of spiral wave has been observed in experiments [11,12] and numerical simulations [13][14][15][16][17][18][19]. The break-up of Turing patterns has been observed in chemical experiments [20] and numerical simulations [21][22][23].…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…[26]-identical to the one for the standard meandering transition-characterizes the spiral transition to alternans. Yet, in contrast to models of complex-oscillatory media, the transition itself does not seem to be a resonant 2 : 1 Hopf bifurcation but rather a nonresonant one since the former would lead to a straight drift of the core [26].…”
Section: Spiral Core Motionmentioning
confidence: 93%
“…Spirals with attached SDLs were first observed in numerical model studies of complexoscillatory media [17] and subsequently in experiments on the Belousov-Zhabotinsky reaction in a comparable regime [20][21][22][23][24][25]. The bifurcation from a regular or period-one spiral to a period-two spiral was later put on a solid mathematical foundation by Sandstede et al [26] and identified as a 2 : 1 resonant Hopf bifurcation for models of complex-oscillatory media. One of the important implications of their analytical findings is that period-two spirals drift with a finite velocity.…”
Section: Introductionmentioning
confidence: 98%